SMART SISTEM PADA KENDANG ITIK MANILA (ENTOK) MENGGUNAKAN MIKROKONTROLER - I Gusti Made Ngurah Desnanjaya; Ida Bagus Gede Sarasvananda; Slamet Samsugi (Universitas Teknokrat Indonesia, 2023)
The cold temperature and the cleanliness of the water pond are the main factors for the problems of the goat breeder. When the ducks start to incubate their eggs, the chicks are vulnerable to death because they are not strong enough to face cold temperatures, especially in the rainy season. Water for drinking and bathing the gout is also quickly dirty and smells. This research was carried out with the aim of designing and building an automatic control device on an Arduino Uno-based goat cage whose performance was carried out on setting the cage heating lamp and filling and draining the wild water pond. The tool is designed using a DHT22 sensor, turbidity sensor, ultrasonic sensor, relay, servo motor, 16x2 LCD and arduino uno. The stages of the design process begin with data collection, tool system analysis, tool workflow design, tool placement, and tool testing. The results of the overall test of the automatic control device for filling and draining the water pool as well as the goat's cage heating lamp, the tool works well. It can be seen from the DHT22 sensor readings with an average error of 0.225% so that the heating lamp setting in the cage runs accurately, then the turbidity sensor readings are obtained from accurate analog sensor readings and ultrasonic sensor readings with an average error of 0.06% so that the filling and draining system works well.